Applications of fractional order elements and mem-elements in electronic circuits - Nariman Abdo Khalil Hussein; Ahmed Gomaa Radwan; Ahmed Mohamed Soliman; Lobna Ahmed Said (Cairo : Nariman Abdo Khalil Hussein, 2020)
This work aims to apply the fractional-order elements and mem-elements in analog circuit design. A general {u200E}prototype fractional-order {uFB01}lter based on a two-port network concept with four external impedances is {u200E}investigated. Ten possible generalized topologies are introduced where the necessary network conditions and {u200E}the critical frequencies are presented. Besides, a generalized prototype topology of fractional order inverse {u200E}{uFB01}lters (FOIF) is presented based on operational trans-resistance ampli{uFB01}ers and second-generation {u200E}current conveyor.The fractional-order parameters increase design {uFB02}exibility and controllability, which is {u200E}validated experimentally.The fractional-order systems are extended to memristive element modeling. The {u200E}realization of grounded and {uFB02}oating fractional-order mem-elements (FOMEs) using the generalized emulator.{u200E}Two- and three-port mutators are used to realize different FOMEs employing di{uFB00}erent combinations of impedances.The FOMEs are applied to Chau's circuit showing the effect of fractional-order on the chaotic behavior. Circuit {u200E}simulations and experimental results for the presented circuits are introduced to validate the theoretical {u200E}{uFB01}ndings
Thesis (Ph.D.) - Cairo University - Faculty of Engineering - Department of Electronics and Communications
Issued also as CD
Keywords: Fractional filter and inverse filter; Fractional order elements emulator; Fractional order memelements emulator